Implementation of Local Government Policies in Realizing Child-Friendly Districts to Increase Welfare - Titi Sutiamah; Dey Ravena; Efik Yusdiansyah (Journal La Sociale, 2022)
Children as the nation's successors prove that the rights of children in Indonesia are expressly stated in the constitution. The purpose of this study was to analyze the implementation of the Pangandaran Regent's Regulation Number 79 of 2018 concerning Child Friendly Districts. This type of research uses normative juridical research. The results of this study: First, the implementation of the Pangandaran Regent Regulation Number 79 of 2018 concerning Child-Friendly Districts in realizing Child-Friendly Districts has not met 24 (twenty four) indicators that become the reference for assessing Child-Friendly Districts, so that in 2021 Pangandaran District has not received an award. Child Friendly District. Second, the Implications of Child Friendly Districts in Pangandaran Regency on children's welfare, based on the score from traceability evidence, obtained a score of 416.42 with the percentage of achievement of 24 indicators, only 41.6% of the total value of achievement should be 1,000 points. It can be said that the Child Friendly District in Pangandaran Regency has not had implications for the welfare of children.